Differential effects of antigens from L. braziliensis isolates from disseminated and cutaneous leishmaniasis on in vitro cytokine production - Leopoldo, Paulo de Tarso Gonçalves (2006)
BACKGROUND: Disseminated leishmaniasis is an emerging infectious disease, mostly due to L. braziliensis, which has clinical and histopathological features distinct from cutaneous leishmaniasis. METHODS: In the current study we evaluated the in vitro production of the cytokines IFN-γ, TNF-α, IL-5 and IL-10 by peripheral blood mononuclear cells (PBMC) from 15 disseminated leishmaniasis and 24 cutaneous leishmaniasis patients upon stimulation with L. braziliensis antigens genotyped as disseminated leishmaniasis or cutaneous leishmaniasis isolates. RESULTS: Regardless of the source of L. braziliensis antigens, PBMC from cutaneous leishmaniasis patients produced significantly higher IFN-γ than PBMC from disseminated leishmaniasis patients. Levels of TNF-α by PBMC from cutaneous leishmaniasis patients were significantly higher than disseminated leishmaniasis patients only when stimulated by genotyped cutaneous leishmaniasis antigens. The levels of IL-5 and IL-10 production by PBMC were very low and similar in PBMCs from both disseminated leishmaniasis and cutaneous leishmaniasis patients. The immune response of each patient evaluated by the two L. braziliensis antigens was assessed in a paired analysis in which we showed that L. braziliensis genotyped as disseminated leishmaniasis isolate was more potent than L. braziliensis genotyped as cutaneous leishmaniasis isolate in triggering IFN-γ and TNF-α production in both diseases and IL-5 only in cutaneous leishmaniasis patients. CONCLUSION: This study provides evidence that antigens prepared from genotypically distinct strains of L. braziliensis induce different degrees of immune response. It also indicates that both parasite and host play a role in the outcome of L. braziliensis infection.